2007
DOI: 10.1177/001440290707300403
|View full text |Cite
|
Sign up to set email alerts
|

A National Study of Youth Attitudes toward the Inclusion of Students with Intellectual Disabilities

Abstract: The authors surveyed a national random sample of 5,837 middle school students on their attitudes toward the inclusion of peers with intellectual disabilities (ID). The national sample provided results that were accurate, with a margin of error of ± 1.4%. Findings indicated that youth (a) have limited contact with students with ID in their classrooms and school; (b) perceive students with ID as moderately impaired rather than mildly impaired; (c) believe that students with ID can participate in nonacademic clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
124
0
21

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 25 publications
16
124
0
21
Order By: Relevance
“…The number of schools sampled was not reported in four studies, but ranged from 1 18 to 68 17 in the other studies. The age of participants ranged from 4 to 18 years old; 13 studies reported the school year but not the participants' actual ages.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of schools sampled was not reported in four studies, but ranged from 1 18 to 68 17 in the other studies. The age of participants ranged from 4 to 18 years old; 13 studies reported the school year but not the participants' actual ages.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Furthermore, none of the studies reported confidence intervals. Effect sizes were reported in only four studies; 16,17,46,47 we have, therefore, calculated effect sizes when possible. Additionally, different effect sizes were used for correlational data and for comparing means; therefore, all available effect sizes were transformed into effect size (Cohen's d) to allow comparisons to be made between individual studies.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Multiple studies have also shown that students with more positive attitudes or beliefs about disabilities are more willing to interact with peers with a disability, while less positive thoughts and feelings by SWOD may interfere with and hinder positive interactions between students with and without disabilities (Kalymon et al, 2010;Litvack, Ritchie, & Shore, 2011;Siperstein, Parker, Bardon, & Widaman, 2007). Further, there is general agreement that social environments, and the norms within them, can strongly influence people's behavior (Bronfenbrenner, 1977;Fishbein & Ajzen, 2010).…”
Section: Influences On Intentions and Actionsmentioning
confidence: 99%
“…The Behavioral Intentions Scale (Siperstein et al, 2007) was used to measure the intentions component of the TPB framework. The full scale consists of 12 questions that assess intentions to interact with peers with an intellectual disability.…”
Section: Rating Scale Measuresmentioning
confidence: 99%
“…Four studies examined the attitudes of children with typical development toward children with intellectual disabilities and interpreted that increased experience in engaging with students with intellectual disabilities is related to positive attitudes (Georgiadi et al, 2012;Rillotta & Nettelbeck, 2007;Siperstein et al, 2007). There were not many concrete practical recommendations in these articles, but Siperstein et al (2007) recommended educators engage in a programmatic and systematic approach to develop positive attitudes among youth and perhaps use an Awareness of Disability training program. This program was considered efficient in Rillotta and Nettelbeck's (2007) study.…”
Section: Inclusionmentioning
confidence: 99%